Comparative analysis of sports workers and kinesiologists: a paradox of similar jobs but distinct professional profiles - Esposito, Giovanni; Ceruso, Rosario; Giardullo, Giuseppe; Aliberti, Sara; Raiola, Gaetano (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Purpose. Recently, in Italy, two professions have been defined in the field of sports and physical activities: the sports worker, trained by sports organisations, and the kinesiologist, who holds a degree in exercise and sports sciences. This distinction is essential to ensure quality standards and appropriate regulations, avoiding duplication and confusion among professionals and clients. This study aimed to understand stakeholders’ knowledge regarding the different professional roles involved in preventive and adapted physical activities, basic and advanced physical exercise, and functional re-athletisation.Methods. A sample of 73 operators from gyms and sports centres in the province of Salerno completed a 12-item survey. Descriptive statistics and Fisher’s exact tests were used to analyse the data, along with Cramer’s V coefficient, to evaluate the association between variables.Results. The results show that 40% of participants do not clearly distinguish between kinesiologists involved in preventive and adapted physical activities and sports kinesiologists, while 28.8% had a limited perception, and 4.1% had no knowledge. Fisher’s test revealed limited knowledge about the distinction between roles (p = 0.008, V = 0.5), highlighting the importance of adequate information and training. Additionally, the professional sphere influences the perception of capabilities in designing post-rehabilitation recovery programs, indicating the need for additional training resources (p = 0.003, V = 0.5).Conclusions. Such studies are fundamental for assessing the effectiveness of legislative and training measures in this sector.
Keywords: sport reform; kinesiologists; reathletization; professional figures